Assessment tensions: How climate mitigation futures are marginalized in long-term transport planning. (October 2020) - Witzell, Jacob
Highlights: The paper studies how established practices influence climate mitigation futures. It focuses the assessment practices of Swedish long-term infrastructure planning. Established practices come to define what is considered relevant knowledge. Alternative assessment practices and development directions are marginalized. In effect, democratic discussion on potential mitigation pathways is constrained. Abstract: Deep uncertainties in planning and policy-making related to climate mitigation pathways actualises the need for transport planning practices that embrace exploration and assessments of alternative future development directions. While conventional, forecast-based assessment practices are acknowledged to be of limited relevance in assessing potential trend-breaking developments, those practices have become strongly institutionalised and proven difficult to challenge. Applying a discourse perspective, this paper contributes with a practice-oriented analysis of how knowledge perspectives and established assessment practices influenced the consideration of alternative development directions and policy measures in the Swedish 12-year National Investment Plan for road and rail infrastructure 2018–2029. More specifically, the analysis regards how alternative futures and measures aimed at supporting a more 'transport efficient society' were addressed and assessed. The analysis illuminates a strong influence of established practices over the definition of what is considered relevant knowledge, in constructing an understanding of transport infrastructure investments as insignificant to climate mitigation, and in legitimizing the marginalization of alternative development directions. In effect, the study shows how established practices may result in significant democratic consequences, when public and political discussion over transport futures and climate mitigation pathways is constrained by a narrow span of possible futures presented.